Land Value Capture for Sustainable Urban Development in A Developing City: A Case of Bekasi City, Indonesia - Anggara, Aang; Wijaya, Nurrohman (Department of Urban and Regional Planning, Universitas Diponegoro, 2024)
Developing a city into a sustainable initiative will take much work, especially given the urban governments with limited budgets and knowledge. These situations are significant in the Global South countries, particularly in emerging economies like Indonesia. One potential urban finance is land value capture (LVC). This paper aims to investigate the concept of LVC as land-based financing for sustainable urban development and examine which instruments are suitable and appropriate to be implemented in an emerging metropolitan city, Bekasi City, Indonesia. The city was selected due to its high urbanization rate, population growth, and facing urban financial challenges. We adopted a systematic review in the initial study to find the LVC development concept. This study used three literature databases: Scopus, Google Scholar, and Science Direct, and we found 20 relevant documents. It reveals several discussed themes regarding LVC, such as the adoption of LVC instruments, the role of LVC regulation, and its governance. This study also examines some instruments of LVC that are suitable for implementation in Bekasi City, such as selling air rights based on floor area ratio (FAR), betterment levy, and developer exaction. LVC can be an innovative urban financing instrument for sustainable urban development by capturing the improvement in land value initiated by government or private investments in urban infrastructure, transportation, or other public goods.